Synthesis and Enhanced Cellular Uptake In Vitro of Anti-HER2 Multifunctional Gold Nanoparticles - Cruz, Esteban (Cancers (Basel), 2019)
Nanoparticle carriers offer the possibility of enhanced delivery of therapeutic payloads in tumor tissues due to tumor-selective accumulation through the enhanced permeability and retention effect (EPR). Gold nanoparticles (AuNP), in particular, possess highly appealing features for development as nanomedicines, such as biocompatibility, tunable optical properties and a remarkable ease of surface functionalization. Taking advantage of the latter, several strategies have been designed to increase treatment specificity of gold nanocarriers by attaching monoclonal antibodies on the surface, as a way to promote selective interactions with the targeted cells—an approach referred to as active-targeting. Here, we describe the synthesis of spherical gold nanoparticles surface-functionalized with an anti-HER2 antibody-drug conjugate (ADC) as an active targeting agent that carries a cytotoxic payload. In addition, we enhanced the intracellular delivery properties of the carrier by attaching a cell penetrating peptide to the active-targeted nanoparticles. We demonstrate that the antibody retains high receptor-affinity after the structural modifications performed for drug-conjugation and nanoparticle attachment. Furthermore, we show that antibody attachment increases cellular uptake in HER2 amplified cell lines selectively, and incorporation of the cell penetrating peptide leads to a further increase in cellular internalization. Nanoparticle-bound antibody-drug conjugates retain high antimitotic potency, which could contribute to a higher therapeutic index in high EPR tumors.